APPLICATION OF SYSTEMATIC DESENSITIZATION TECHNIQUES TO OVERCOME ACADEMIC ANXIETY IN BLIND "A" CLIENTS AT SLB-A RPCN PALEMBANG - Suryati, Suryati; Fitri, Hartika Utami; Asih, Wanda Dewi Muro (Jurnal Konseling Pendidikan Islam, 2025)
This research aims to determine the description of academic anxiety in client "A" at SLB-A PRPCN Palembang before systematic desensitization techniques are given. This research method uses a qualitative approach and case study research methods. Data collection uses interview, observation and documentation techniques. The research subject consisted of one person, namely client "A" who was blind. The results of this research show that before the application of this systematic desensitization technique, client "A’s" academic anxiety picture was in the form of concerns about his own abilities in mobility orientation, having a fear of failing in mobility orientation, having negative thoughts about mobility orientation, having difficulty taking decision in mobility orientation, feeling excessive heart rate when going to mobility orientation, feeling sweat on the palms during mobility orientation, and experiencing difficulty moving in a new environment during mobility orientation. Furthermore, after implementing this systematic desensitization technique, client "A" began to experience changes, namely the client began to worry less about himself, began to no longer be afraid that he would fail in mobility orientation, was able to control negative thoughts about mobility orientation, and began to be able to make decisions. itself in mobility orientation, reduced heart rate. the sweat on the palms has begun to decrease and I have started to dare to move in new environments during mobility orientation. This shows that the application of this systematic desensitization technique was successful in overcoming academic anxiety in client "A" who was blind at SLB-A PRPCN Palembang.